2018
DOI: 10.1111/1346-8138.14484
|View full text |Cite
|
Sign up to set email alerts
|

Mild hyperbaric oxygen activates the proliferation of epidermal basal cells in aged mice

Abstract: The proliferation of epidermal basal cells decreases with age. This study examined the effects of exposure to mild hyperbaric oxygen on the proliferative activity of epidermal basal cells in aged mouse skin. Hairless mice aged 5, 34 and 55 weeks were exposed to mild hyperbaric oxygen at 1266 hPa with 36% oxygen for 6 h/day for 1 or 2 weeks. Skin samples were then collected from the back area to evaluate epidermal thickness and the number and proliferative activity of epidermal basal cells. Exposure to mild hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The increase in angiogenesis and collagen density was in line with previous reports of HBOT in skin conditions including wound healing [ 26 , 28 ] and compromised grafts and flaps [ 29 ]. In the epidermis, the intrinsic physiological aging can be characterized by a generalized epidermal atrophy [ 151 ] mostly due to a decrease in proliferative activity and turnover rate of epidermal basal cells [ 152 , 154 ]. It is reported that exposure to mild hyperbaric oxygen with 36% oxygen reversed the age-related decline in proliferative activity of epidermal basal cells in the skin of aged mice [ 154 ].…”
Section: Therapeutic Implications Of Hbot In Aging Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in angiogenesis and collagen density was in line with previous reports of HBOT in skin conditions including wound healing [ 26 , 28 ] and compromised grafts and flaps [ 29 ]. In the epidermis, the intrinsic physiological aging can be characterized by a generalized epidermal atrophy [ 151 ] mostly due to a decrease in proliferative activity and turnover rate of epidermal basal cells [ 152 , 154 ]. It is reported that exposure to mild hyperbaric oxygen with 36% oxygen reversed the age-related decline in proliferative activity of epidermal basal cells in the skin of aged mice [ 154 ].…”
Section: Therapeutic Implications Of Hbot In Aging Interventionmentioning
confidence: 99%
“…In the epidermis, the intrinsic physiological aging can be characterized by a generalized epidermal atrophy [ 151 ] mostly due to a decrease in proliferative activity and turnover rate of epidermal basal cells [ 152 , 154 ]. It is reported that exposure to mild hyperbaric oxygen with 36% oxygen reversed the age-related decline in proliferative activity of epidermal basal cells in the skin of aged mice [ 154 ]. These results supported the point that the intrinsically aged skin can be partially revitalized by hyperbaric oxygen, whose potentiality has not been sufficiently realized.…”
Section: Therapeutic Implications Of Hbot In Aging Interventionmentioning
confidence: 99%
“…Proliferation of epidermal basal cells decreases with age [59]. Exposure to mild hyperbaric oxygen has been reported to accelerate the proliferative activity of epidermal basal cells in aged mouse skin [60]. An adequate oxygen supply from exposure to mild hyperbaric oxygen may accelerate the turnover rate of aged skin by enhancing the proliferative activity of epidermal basal cells.…”
Section: Pigmentation and Proliferationmentioning
confidence: 99%
“…An adequate oxygen supply from exposure to mild hyperbaric oxygen may accelerate the turnover rate of aged skin by enhancing the proliferative activity of epidermal basal cells. Therefore, the dissolved oxygen, which is increased by exposure to mild hyperbaric oxygen, is considered to diffuse from the dermis to the epidermis through blood microcirculation, thus accelerating proliferation of epidermal basal cells and inhibiting epidermal aging [60]. Suppression of ultraviolet B irradiation-induced pigmentation is due, at least in part, to the reduction in prostaglandin synthesis via the inhibition of cyclooxygenase by indomethacin, and to the induction of annexin or lipocortin by corticosteroids [61].…”
Section: Pigmentation and Proliferationmentioning
confidence: 99%
“…Hachmo et al [ 195 ] reported the effect of hyperbaric oxygen in the prevention of telomere shortening and immunosenescence by the clearance of senescent immune cells. In this line, other studies have reported the same results in the aging skin, through the acceleration of epidermal basal cells proliferation [ 196 ], in the endothelial cells, where it induces antioxidants expression [ 197 ] and also in the brain, where HBOT appears to improve the cerebral blood flow [ 198 ], restoring cognitive parameters, hippocampal functions and even improved insulin resistance in both normal-weigh and obese aging rats [ 199 ].…”
Section: Translational and Potential Applications Of Hbotmentioning
confidence: 74%